Proposal of new PAPR reduction method for OFDM signal by using permutation sequences - Boonsrimuang, Pornpawit; Limwattanachai, Kanchana; Boonsrimuang, Pisit; Kobayashi, Hideo (My University, 2012)
Many PAPR reduction techniques for OFDM signal have been proposed up to today, which can be classified into two major methods as the distortion and distortion-less methods. The most of distortion-less methods show better PAPR performance without degradation of BER performance. This paper proposes a novel distortion-less PAPR reduction method which employs the permutation sequence in the frequency domain with embedded side information. The feature of proposed method is to achieve the better PAPR performance with very few side information for the correct demodulation of data information at the receiver. This paper presents various computer simulation results to verify the effectiveness of proposed method as comparing with the conventional OFDM method in the non-linear channel. © 2012 GIRI.
Keywords: Non-linear channel; OFDM; PAPR